Analisis Sustainable Development Goals (SDGs) 12 Terhadap Kinerja Lingkungan PT Pupuk Indonesia - Aryanta, Dewa Wahyu; Bayangkara, Ida Bagus Ketut (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study analyze the implementation of Sustainable Development Goal (SDGs) 12 responsible consumption and production on the environmental performance of PT Pupuk Indonesia (Persero). Using a descriptive qualitative approach and thematic analysis, data were collected from sustainability reports and official company documents. The findings reveal that the company has incorporated SDGs 12 principles into its policies and operations through ISO 14001 certification, Green and Gold PROPER ratings, a decarbonization strategy toward Net Zero Emissions by 2060, and 3R-based waste management programs. The company also applies GRI-based sustainability reporting to ensure transparency and good governance. The study concludes that PT Pupuk Indonesia has taken concrete and progressive steps in supporting SDGs 12, although there is still room to enhance sustainable strategies in the future